Zealots for souls: Dominican narratives of Self-Understanding during observant reforms, c. 1388-1517 - Huijbers, Anne (Quellen und Forschungen zur Geschichte des Dominikanerordens, 2018)
Zealots for souls draws attention to the impact of the Observant reforms within the Order of Preachers, and ambitiously stirs up a broad scope of questions pertaining to the institutional narratives produced within the order between c. 1388 and 1517. Through the narratives and the forms of remembrance they fostered, the author traces the development of contemporary characteristics of the Dominican self-understanding. The book shows the fluid boundaries between the genres (order chronicles, convent chronicles, collective biographies), highlights the interplay between the narrative and the intended audience, addresses the complex question of authorship, and assesses the indebtedness of 'modern' (printed) narratives to older chronicles or biographical collections. The book demonstrates that the majority of the extant institutional narratives were written by Observant Dominicans, who strived for the internal reform of their order. They wrote history to justify their own reform agenda and therefore produced invariably partisan chronicles. The work's method is widely applicable and contributes to further reassessment of institutional narratives as sources for the analysis of religious and intellectual transformations.